2020
DOI: 10.1186/s12879-020-05290-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of tuberculosis infection among adults visiting anti-retroviral treatment center at east and west Gojjam, northwest, Ethiopia, 2017

Abstract: Background Tuberculosis is a serious health risk, for people living with human immune deficiency virus worldwide, and the burden of TB/HIV infection is still high in Ethiopia in particular. Therefore, the aim of this study was to determine the predictors of tuberculosis infection among adults visiting anti-retroviral treatment center in East and West Gojjam, northwest, Ethiopia. Methods Institution based unmatched case-control study was employed to determine the predict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
(51 reference statements)
8
8
0
Order By: Relevance
“…Most of the HIV- infected patients in this study were in WHO clinical stage I and had a working functional class. Our finding is comparable with reports from Hawassa [ 10 ], Gondar [ 11 ], Debre Tabor [ 14 ], Debre Markos [ 13 ], and Gojjam [ 15 ]. Less than a quarter (23.0%) of the patients had CD4 cell counts of less than 200 cell/μL.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most of the HIV- infected patients in this study were in WHO clinical stage I and had a working functional class. Our finding is comparable with reports from Hawassa [ 10 ], Gondar [ 11 ], Debre Tabor [ 14 ], Debre Markos [ 13 ], and Gojjam [ 15 ]. Less than a quarter (23.0%) of the patients had CD4 cell counts of less than 200 cell/μL.…”
Section: Discussionsupporting
confidence: 92%
“…Less than a quarter (23.0%) of the patients had CD4 cell counts of less than 200 cell/μL. Comparable findings were reported from Yirgalem [ 7 ] and Gojjam [ 15 ]. However, relatively higher findings were reported from Gondar [ 11 ] and Debre Tabor [ 14 ], and Amhara region [ 9 ].…”
Section: Discussionsupporting
confidence: 62%
“…Other independent risk factors that affected TB morbidity in the study groups such as CD4 count less than 200 cells/µL, decreased level of adherence to ART, and history of malnutrition were more or less similar to findings of other studies reported elsewhere [ 9 , 37 ]. The first four risk factors, directly or indirectly, could make the person susceptible to TB by compromising the immune system, which indicates the importance of lifestyle changes that boost immunity.…”
Section: Discussionsupporting
confidence: 88%
“…Other independent risk factors that affected TB morbidity in the study groups such as CD4 count less than 200 cells/lL, decreased level of While computing these variables, we excluded children less than 16 years of age from the analysis (N = 6178) as they are not related to pediatric populations Fig. 4 Kaplan-Meier plot: estimating survival probability versus time without tuberculosis in the isoniazid exposed and unexposed groups using survival regression analysis model adherence to ART, and history of malnutrition were more or less similar to findings of other studies reported elsewhere [9,37]. The first four risk factors, directly or indirectly, could make the person susceptible to TB by compromising the immune system, which indicates the importance of lifestyle changes that boost immunity.…”
Section: Discussionsupporting
confidence: 55%
“…Majority of the study focused on prevalence and predictors of TB in HIV patients. In order to determine the important determinants of TB co-infection in HIV patients, most of the methodologies in the literature used logistic regression with outcome being the TB's viability through follow up time of HIV/AIDS patients taking ART treatment [12,14,17]. In logistic regression, our interest is to study how risk factors were associated with the presence or absence of a disease( or an event) without taking into account the effect of time [15].…”
Section: Introductionmentioning
confidence: 99%